Pathology of multiple endocrine neoplasia syndrome 2A - Majewski, Przemysław; Janicka-Jedyńska, Małgorzata (Contemporary Oncology/Współczesna Onkologia, 2005)
MEN type 2A involves thyroid C cells, adrenal medulla and parathyroids. Medullary thyroid carcinoma (MTC) develops as the first neoplasm. C-cell hyperplasia is the precursor of MTC. In MEN 2A, MTC is multifocal and bilateral and the age of diagnosis tends to be younger in contrast to a sporadic form. MCT is firm and circumscribed. The pattern of growth is that of tumor cells arranged in nests separated by fibrous tissue with many capillaries. The stroma frequently contains amyloid. There are many microscopic subtypes of MTC thus immunohistochemistry is necessary for differential diagnosis. The stage is most important for prognosis. Prognosis is better for patients with MTC and MEN 2A than MEN 2B and the sporadic form. MTC infiltrates locally and metastasizes to lymph nodes, liver, bones and lungs. About 10 years after the diagnosis of MTC 30-50% of patients with MEN 2A develop pheochromocytoma, which is typically bilateral and multicentric. Pheochromocytoma is composed of large cells that form solid areas separated by fibrous tissue with many capillaries. There are no absolute criteria that distinguish benign pheochromocytomas from malignant ones. Only distant metastases are the evidence of pheochromocytoma malignancy. In parathyroid hyperplasia all four glands are enlarged. Adenoma of parathyroid is a single lesion.